Examining The Conflict Of Ukraine And Russia In Terms Of Military Strength, Strategy And Risks - Rizalah, Taufik; Khaerudin Khaerudin; Sri yanto (CV. AFDIFAL MAJU BERKAH, 2025)
The conflict between Russia and Ukraine has become an ongoing issue in the international sphere. Starting from the dissolution of the Soviet Union in 1991, Ukraine and other countries formed under the umbrella of the Soviet Union were granted independence. But several years later, in 2014, Russia began to attack Ukraine by annexing Crimea, a strategic region that also threatened the lives of the Ukrainian people who were its native inhabitants. This action was quickly condemned by the international community and resulted in sanctions against Russia. However, in 2021, in November, Russia again gathered troops in the Ukrainian border region. It was found that the strength of the Russian army was greater than that of Ukraine, especially in the fields of resources and military technology. However, Ukraine can face these limitations by implementing a military strategy with guerrillas and sabotage as well as assistance from the support of allied. Irregular and Hybrid Warfare tactics and strategies have also been carried out by both parties. Mediation needs to be carried out by the UN, the European Union and each country to find a good solution